1990
DOI: 10.1056/nejm199006213222503
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane Biosynthesis and Platelet Function in Type II Diabetes Mellitus

Abstract: It has been suggested that platelet hyperreactivity in patients with diabetes mellitus is associated with increased platelet production of thromboxane. We therefore compared the excretion of a thromboxane metabolite and platelet function in 50 patients with Type II diabetes mellitus who had normal renal function and clinical evidence of macrovascular disease and in 32 healthy controls. The mean (+/- SD) excretion rate of urinary 11-dehydro-thromboxane B2 was significantly higher in the patients than in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
306
0
8

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 568 publications
(331 citation statements)
references
References 22 publications
17
306
0
8
Order By: Relevance
“…Patients with diabetes also have impaired platelet function characterized by increased levels of plasminogen activator inhibitor-1 and adhesion molecules. 15,16 This enhances platelet adhesiveness and hyperaggregability and predisposes to coronary thrombosis, which may ultimately affect long-term vein graft patency. Intravenous infusions of insulin after CABG surgery have been shown to decrease levels of free fatty acids and increase myocardial uptake of glucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with diabetes also have impaired platelet function characterized by increased levels of plasminogen activator inhibitor-1 and adhesion molecules. 15,16 This enhances platelet adhesiveness and hyperaggregability and predisposes to coronary thrombosis, which may ultimately affect long-term vein graft patency. Intravenous infusions of insulin after CABG surgery have been shown to decrease levels of free fatty acids and increase myocardial uptake of glucose.…”
Section: Discussionmentioning
confidence: 99%
“…It upwardly regulates the L-arginine-NO pathway, which improves endothelial function, and it decreases serum levels of plasminogen activator inhibitor-1. 15 Several studies have shown that hyperglycemia is associated with adverse outcomes during acute coronary syndromes. Wahab and colleagues 19 studied the effects of increased blood glucose in 1664 patients admitted with an acute MI.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hyperglycemia has been clearly identified as a causal factor for in vivo platelet activation [11]. Our group firstly demonstrated enhanced thromboxane (TX) biosynthesis in T2D, providing evidence for its platelet origin.…”
mentioning
confidence: 97%
“…Our group firstly demonstrated enhanced thromboxane (TX) biosynthesis in T2D, providing evidence for its platelet origin. Moreover, tight metabolic control led to reduction of TX metabolite urinary levels [11]. Interestingly, inflammatory mediators (such as CD40L) derived from platelets expand the functional repertoire of platelets from players of hemostasis and thrombosis to powerful amplifiers of inflammation by promoting the release of cytokines and chemokines, cell activation and cell-cell interactions [12].…”
mentioning
confidence: 99%
“…Increased platelet aggregation in DM was recognized already in 1965 [20]; since then many studies have demonstrated that platelet degranulation and synthesis of TX derivatives mediating further platelet activation are increased in DM [21,22], whereas platelet-mediated vasodilatation is impaired [23]. Furthermore, platelets from DM patients have been shown to have diminished sensitivity to natural antiaggregating Fig.…”
Section: Determinants Of In Vivo Platelet Activation In Diabetes Mellmentioning
confidence: 99%